CCD CAMERA WITHOUT COOLING - Shahrukhanov, O. Sh. (Одеські астрономічні публікації, 2017)
The device with the parameters taking one's intermediate stand between the standard TV and CCD cameras with cooling is developed. This camera works without cooling. Accumulation time can be established in the limits from 1 up to 16 TV frames. The results of trial measurements and possibilities for using of the given device are illustrated in this work.